Doped-magnesium manganese oxide cathode for rechargeable magnesium batteries / Nurhidayu Harudin - Nurhidayu , Harudin (2021)
Magnesium has numerous good characteristics that make it attractive as an electrode material for rechargeable batteries. There are many advantages of Magnesium (Mg) such as available in abundance, ease of handling, low toxicity and environmental friendly. Due to its benefits, magnesium ion battery can be considered as an alternative to lithium in future. In the present work, the improvement electrochemical properties of magnesium-based cathode material, MgMn2O4 was done by adding calcium (Ca) and strontium (Sr) as dopant i.e MgMn2-xCaxO4 and MgMn2-xSrxO4. These materials with compositions of x=0.1,0.2,0.3,0.4,0.5 were synthesized by self-propagating combustion method using citric acid as a reducing agent. The precursors obtained were annealed at temperatures of 700C and 800C for 24 hours. The electrochemical studies were performed by using Linear Sweep Voltammetry (LSV) and Cyclic Voltammetry (CV) to determine electrochemical stability and properties of the prepared samples using 1M of magnesium trifluoromethane sulfonate Mg(CF3SO3)2 electrolyte. The magnesium ion cells were fabricated using the optimized cathode materials and the cell performances were be studied by galvanostatic charge-discharge test. At temperature 700°C, the specific capacity obtained from MgMn1.8Ca0.2O4 and MgMn1.8Sr0.2O4 at first cycle was 60 mAh g-1 and 40 mAh g-1 respectively. At temperature 800°C, the fabricated cells conveyed the specific capacity of 138 mAh g-1 and 160 mAh g-1 for Ca and Sr doped samples respectively. Therefore, it can be stated that both Ca and Sr doped systems of MgMn2O4 based cathode materials enhances a good electrochemical properties thus improving the battery performances.